Metallurgical and mechanical properties of SiC/ B4C reinforced with aluminum composites synthesized by mechanical alloying. (2021) - Pandiyarajan, R.; Prabakaran, M.P.; Rajkumar, T.; Vetrivel Kumar, K.; Manikandan, R.
Abstract: In advanced engineering dynamic environment applications demands in high performance and new composite materials. The hybrid composite materials are satisfying the recent engineering application demands and also improve the particular unique properties of composite materials. In present work, investigate the mechanical and metallurgical characterizations of composite materials fabricated by powder metallurgy pressure die casting process for various weight percentage of Silicon carbide (SiC), Boron carbide (B4C) reinforced with aluminum. The main objective of the paper is to improve the metallurgical and hardness properties of aluminum matrix composite materials. The Scanning Electron Microscopy (SEM) and Energy Dispersive X- RAY (EDX) analysis used to identify the humongous dispersion of hybrid composite. The hardness test was performed and it was found that the hybrid composite materials had produced the superior than base aluminum